NETosis: A key player in autoimmunity, COVID-19, and long COVID - Diana M. Monsalve; Yeny Acosta-Ampudia; Nicolás Guerrero Acosta; Mariana Celis-Andrade; Ali Şahin; Ahsen Morva Yilmaz; Yehuda Shoenfeld; Carolina Ramírez-Santana (Journal of Translational Autoimmunity)
NETosis, the process through which neutrophils release neutrophil extracellular traps (NETs), has emerged as a crucial mechanism in host defense and the pathogenesis of autoimmune responses. During the SARS-CoV-2 pandemic, this process received significant attention due to the central role of neutrophil recruitment and activation in infection control. However, elevated neutrophil levels and dysregulated NET formation have been linked to coagulopathy and endothelial damage, correlating with disease severity and poor prognosis in COVID-19. Moreover, it is known that SARS-CoV-2 can induce persistent low-grade systemic inflammation, known as long COVID, although the underlying causes remain unclear. It has been increasingly acknowledged that excessive NETosis and NET generation contribute to further pathophysiological abnormalities following SARS-CoV-2 infection. This review provides an updated overview of the role of NETosis in autoimmune diseases, but also the relationship between COVID-19 and long COVID with autoimmunity (e.g., latent and overt autoimmunity, molecular mimicry, epitope spreading) and NETosis (e.g., immune responses, NET markers). Finally, we discuss potential therapeutic strategies targeting dysregulated NETosis to mitigate the severe complications of COVID-19 and long COVID.